2005
DOI: 10.1093/eurpub/cki052
|View full text |Cite
|
Sign up to set email alerts
|

Periconceptional smoking and male : female ratio of newborns

Abstract: We have analysed data collected on 1962 women who gave birth at 37 or more weeks of gestation to health infants (excluding those with a low birth weight and twins). In comparison with non-smoking parents, the odds ratio (OR) of being male was lower than unity for offsprings of both smoking parents, but no clear relationship however emerged between the risk of giving birth to a male, and the number of cigarettes smoked per day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…However, it is unexpected that association between male infertility and a female-biased offspring sex ratio was not found (11). Moreover, many factors are sometimes associated with the sex ratio at birth, including paternal age >40 years of age (12,13), maternal age >40 years of age ( 14) multiparity (14,15), parental smoking (16,17), and assisted reproduction technology (intracytoplasmic sperm injection [18,19], blastocyst culture [20], and embryo culture media [21]). Until now, no evidence has shown an association between male BMI and the sex ratio at birth after assisted reproduction, but a large number of studies have suggested that there is an association between an elevated paternal BMI around conception with a higher BMI of offspring (22,23), and there is a potential association between the paternal health status and health of the offspring (24)(25)(26).…”
mentioning
confidence: 99%
“…However, it is unexpected that association between male infertility and a female-biased offspring sex ratio was not found (11). Moreover, many factors are sometimes associated with the sex ratio at birth, including paternal age >40 years of age (12,13), maternal age >40 years of age ( 14) multiparity (14,15), parental smoking (16,17), and assisted reproduction technology (intracytoplasmic sperm injection [18,19], blastocyst culture [20], and embryo culture media [21]). Until now, no evidence has shown an association between male BMI and the sex ratio at birth after assisted reproduction, but a large number of studies have suggested that there is an association between an elevated paternal BMI around conception with a higher BMI of offspring (22,23), and there is a potential association between the paternal health status and health of the offspring (24)(25)(26).…”
mentioning
confidence: 99%
“…Finally, until now, diet and lifestyle have been overlooked as risk co-modulators. Tobacco smoke is a recognized risk factor for placental development and other adverse pregnancy outcomes, and it is recognized to have EDC-like activities (Parazzini et al, 2005;George et al, 2006;Cooper and Moley, 2008;Shields et al, 2009). It is plausible that the fertility and fecundity of smoking women would also be more vulnerable to EDC exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It is less widely known that smoking can also disrupt endocrine function, with effects ranging from disrupted conception (Cooper and Moley, 2008) to various alterations of fetal hormone balance that might affect pregnancy outcome or developmental programming (Shields et al, 2009). Parazzini et al (2005) analysed data collected in 1962 women who gave birth at 37 or more weeks of gestation to healthy infants (excluding those with a low birthweight and twins). Women were asked about the smoking habits of the fathers of the newborns during the periconceptional period; thus, the smoking habits of the fathers were reported by the women.…”
Section: Pregnancy Outcomesmentioning
confidence: 99%
“…Outros fatores secundários descritos na literatura que influenciaram na razão sexual seriam: raça, idade dos pais, paridade (96)(97)(98) e o tempo entre o intercurso sexual e a ovulação (99) . Alguns estudos mostraram influência do tabagismo ativo dos pais em aumentar a proporção de nascimentos do sexo feminino (100)(101)(102) . Em relação às estações do ano, um estudo constatou uma influência nas taxas de sucesso de concepção (103) , mas quanto à influência na razão sexual dos nascimentos, os resultados são conflitantes (104)(105)(106)(107) .…”
Section: Influência Da Poluição Na Determinação Do Sexo Do Rnunclassified
“…Em relação às covariáveis avaliadas nos modelos de regressão, não foi observada influência significativa de paridade, idade, e tabagismo materno na determinação do sexo. Alguns estudos encontraram uma influência dose-resposta entre tabagismo ativo e diminuição na proporção de nascimentos do sexo masculino (100)(101)(102) (155) . Dessa forma, o presente estudo avalia adequadamente o período de exposição à poluição (preconcepcional) e corrobora os resultados anteriores.…”
Section: Sexo Do Rnunclassified